2011
DOI: 10.4238/vol10-1gmr907
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative compatibility and genetic analysis of Colletotrichum lindemuthianum isolates from Brazil

Abstract: ABSTRACT. The causal agent of common bean anthracnose, Colletotrichum lindemuthianum, has considerable genetic and pathogenic variability, which makes the development of resistant cultivars difficult. We examined variability within and between Brazilian pathotypes of C. lindemuthianum through the identification of vegetative compatibility groups (VCGs) and by RAPD analysis. Two hundred and ninety-five nit mutants were obtained from 47 isolates of various pathotypes of the fungus collected from different region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
(50 reference statements)
2
7
1
Order By: Relevance
“…Thus, although the development of vegetative heterokaryotic cells may be advantageous for filamentous fungi, the genetic mechanism of vegetative incompatibility may also restrict the process between two genetically different individuals. It has recently been shown that genetic diversity in natural populations of C. lindemuthianum is considerable and that numerous vegetative compatibility groups are present [14]. However, our knowledge of vegetative incompatibility in Colletotrichum species is still very limited [7], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the development of vegetative heterokaryotic cells may be advantageous for filamentous fungi, the genetic mechanism of vegetative incompatibility may also restrict the process between two genetically different individuals. It has recently been shown that genetic diversity in natural populations of C. lindemuthianum is considerable and that numerous vegetative compatibility groups are present [14]. However, our knowledge of vegetative incompatibility in Colletotrichum species is still very limited [7], [14].…”
Section: Introductionmentioning
confidence: 99%
“…It was not possible to prove the parasexual cycle in this study, which requires auxotrophic mutants as described for other species (Stromnaes and Garber, 1963;Castro-Prado et al, 2007;Milgroom et al, 2009;Barcelos et al, 2011). Other tools have recently been used such as nucleus-targeting fluorescent proteins and insertion of hygromycin-and phleomycin-resistance genes.…”
Section: Discussionmentioning
confidence: 98%
“…Genetically different isolates of C. lindemuthianum showed the capacity for hyphal anastomosis between one another, which could contribute to increased genetic variability (Ishikawa et al, 2008). However, studies using nit mutants showed a predominance of vegetative incompatibility in C. lindemuthianum (Castro-Prado et al, 2007;Barcelos et al, 2011), and despite anastomosis formation, vegetative incompatibility reaction occurs afterwards, leading to cell death (Ishikawa et al, 2012).…”
Section: Angular Leaf Spot Of Common Bean (Phaseolus Vulgaris L) Is mentioning
confidence: 99%
“…The use of phytopathogen-resistant cultivars is the main strategy to contain this disease in Brazil (Damasceno e Silva et al 2007). However, due to the large genetic variability of C. lindemuthianum, the breakdown of resistance prevents the use of cultivars for long periods of time, thus hindering the establishment of a permanent solution to the disease (Rodriguez-Guera et al 2003;Ansari et al 2004;Mahuku and Riascos 2004;Barcellos et al 2011). The large genetic and pathogenic variability found in Colletotrichum species has been extensively studied, and it can be partially explained by recombinant events and mutations caused by the presence of transposons (Casela and Frederiksen 1994;Santos et al 2012), and by the presence of anastomoses among conidia (Roca et al 2003;Castro-Prado et al 2007;Rosada et al 2010;Franco et al 2011).…”
Section: Introductionmentioning
confidence: 99%